Conjugated polymers with anionic dyes: Synthesis, properties, and sensing ability for nucleosides, DNA, and BSA. Issue 33 (4th April 2021) - Yamaguchi, Isao; Tariqul, Islam M. D.; Wang, Aohan
Abstract: The reaction of N ‐(2, 4‐dinitrophenyl)pyridinium chloride (salt[Cl − ]) with sodium salts of anionic dyes, such as acid red 52 (AR52), acid violet 49 (AV49), and coomassie brilliant blue G‐250 (CBBG250) involves an anion exchange between the chloride anion of salt(Cl − ) and sulfonium anion of the dyes, resulting in the generation of novel Zincke salts, namely, salt(AR52), salt(AV49), and salt(CBBG250), respectively. Reactions of salt(AR52), salt(AV49), and salt(CBBG250) with piperazine in the absence of catalysts resulted in the opening of the pyridinium ring to yield ionic polymers comprising units of 5‐piperazinium‐2, 4‐dienylideneammonium and the corresponding dye anion, namely polymer(AR52), polymer(AV49), and polymer(SBBG250), respectively. The corresponding model compounds for the polymers were also synthesized by reacting salt(AR52), salt(AV49), and salt(CBBG250) with piperidine. Polymer(AV49) and polymer(SBBG250) were found to be suitable for the detection of nucleosides, DNA, and proteins, realized by monitoring the changes in their UV–vis absorption spectra, arising from the anionic dyes within the polymers. The polymers and the model compounds were electrochemically oxidized in solution. Abstract :